A numerical study on chloride transport in alkali-activated fly ash/slag concretes. (April 2023) - Liu, Qing-feng; Cai, Yuxin; Peng, Hui; Meng, Zhaozheng; Mundra, Shishir; Castel, Arnaud
Abstract: Alkali-activated binders for concrete composites are emerging as the available low-embodied-carbon alternatives to ordinary Portland cement (OPC). Despite decades of research, the durability of alkali-activated concrete remains a concern, especially the issues related to chloride penetration and the potential for chloride-induced corrosion of embedded steel bars. In this study, a multi-phase, multi-component ionic numerical model is developed to investigate the chloride transport in alkali-activated fly ash/slag (AAFS) concretes. The model framework considers the porosity of concrete, the chloride binding, and the electrochemical coupling between multi-species. Based on the proposed model, the parametric studies of a series of influencing factors on both chloride transport and initiation time of reinforcement corrosion are performed and discussed. The results indicate that the slag content and the water to binder ratio are the dominant factors affecting chloride penetration and corrosion initiation time of steel bars in AAFS concretes due to their greater contributions to reduce the porosity, while the aggregate volume fraction presents a limited effect compared with other factors. The transport model proposed in this study brings insights to the prediction of the service life of alkali-activated reinforced concrete structures. Highlights: A multi-phase, multi-species model is developed to investigate the chloride transport behaviour in the binary AAFS system. The proposed model considers the porosity of concrete, chloride binding and electrochemical coupling between multi-species. The influence mechanism of relevant factors on both chloride penetration and reinforcement corrosion onset is discussed. Slag content is proved to be the most important influencing factor on chloride transport in AAFS concretes.